Observations of compact sources in galaxy clusters using MUSTANG2. Issue 2 (22nd September 2021) - Dicker, Simon R; Battistelli, Elia S; Bhandarkar, Tanay; Devlin, Mark J; Duff, Shannon M; Hilton, Gene; Hilton, Matt; Hincks, Adam D; Hubmayr, Johannes; Huffenberger, Kevin; Hughes, John P; Di Mascolo, Luca; et al.
ABSTRACT: Compact sources can cause scatter in the scaling relationships between the amplitude of the thermal Sunyaev–Zel'dovich Effect (tSZE) in galaxy clusters and cluster mass. Estimates of the importance of this scatter vary – largely due to limited data on sources in clusters at the frequencies at which tSZE cluster surveys operate. In this paper, we present 90 GHz compact source measurements from a sample of 30 clusters observed using the MUSTANG2 instrument on the Green Bank Telescope. We present simulations of how a source's flux density, spectral index, and angular separation from the cluster's centre affect the measured tSZE in clusters detected by the Atacama Cosmology Telescope (ACT). By comparing the MUSTANG2 measurements with these simulations we calibrate an empirical relationship between 1.4 GHz flux densities from radio surveys and source contamination in ACT tSZE measurements. We find 3 per cent of the ACT clusters have more than a 20 per cent decrease in Compton- y but another 3 per cent have a 10 per cent increase in the Compton- y due to the matched filters used to find clusters. As sources affect the measured tSZE signal and hence the likelihood that a cluster will be detected, testing the level of source contamination in the tSZE signal using a tSZE-selected catalogue is inherently biased. We confirm this by comparing the ACT tSZE catalogue with optically and X-ray-selected cluster catalogues. There is a strong case for a large, high-resolution survey of clusters to better characterize their source population.